Effects of watering regime on the morphological, physiological and functional traits of seedlings of cacao provenances under screen house conditions - Olayemi, Laureta; Agele, Samuel; Adejobi, Adejobi; Aiyelari, Peter (Journal of Plant Stress Physiology, 2022)
In the present study, morphological and physiological responses of cocoa provenances to watering regimes under screen house conditions and the implications of the measured variables as drought tolerance strategy in Theobroma was discussed. A 4 by 3 factorial scheme involving four cacao provenances and watering regimes (well watering at full field capacity, 60 and 40% field capacity: 1.5, 0.9 and 0.6 L/plant at each watering event) the cocoa genotypes evaluated are PA 150 Series (the elite varieties), F3 Amazon and Amelonado. Observations were made on the morphological and physiological traits of seedlings of the cacao genotypes affected by watering regimes. The measured variables were deployed to rank the drought performance of cacao genotypes following nursery desiccation studies. Data on root and shoot biomass, water use, stomatal conductance, proline, water soluble carbohydrate and leaf chlorophyll concentrations of cacao seedlings were collected. The results showed that root zone moisture status affected the morphological and physiological characteristics of cacao provenances. Differences were obtained in root and shoot biomass, water use, the densities of stomatal and its conductance of gases, and the concentrations of leaf chlorophyll, and shoot and leaf proline and water soluble carbohydrates among the watering regimes imposed. Cacao provenances evaluated also differed in their responses to watering regimes and in morphological and physiological characters. The imposed root zone moisture scenarios elicited differences in the responses of cacao provenances evaluated. Most of the measured morphological and physiological variables were driven by root zone moisture status among cacao provenances, the measured traits appeared to have played important roles as root zone moisture deficit stress tolerance mechanisms in cacao. Seedlings of cocoa provenances had better vigour of growth when grown under 100 and 60% field capacity watering compared with 40% FC. Adequacy of soil moisture promotes growth and physiological functions in the seedlings of cacao provenances tested. The measured morpho-physiological variables were statistically superior under well watered situations (100% FC) compared with the 40% FC. The results confirmed that cocoa seedlings cannot withstand soil moisture deficit stress as was obtained for seedlings that were watered with 40% FC. It is recommended that watering cacao seedlings at full field capacity (FC) and at 70% FC (mild root zone moisture stress) will ensure the production of vigorous seedlings of cacao in the nursery.